Hypoxia-related signatures predicts survival, immunosuppression and PARP inhibitor resistance in HCC - Min Su; Haibo Duan; Yu Gu; Jianfu Zhao (Discover Oncology)
Abstract Background Despite extensive research on hypoxia in hepatocellular carcinoma (HCC), previous studies have relied on pre-existing hypoxia gene sets, limiting their specificity. We developed a novel approach using direct comparison of hypoxic versus normoxic HCC cell lines to establish a more precise hypoxia signature. Methods Through differential gene expression analysis of HCC cells under controlled oxygen conditions (GSE185969) and integration with TCGA-LIHC data, we identified and validated a highly specific 29-gene hypoxia signature. We performed comprehensive immune profiling and genomic instability analyses using multi-omics approaches. Results Our HCC-specific hypoxia signature demonstrated superior prognostic value (AUC: 0.805, 0.805, 0.748 at 1/3/5 years) compared to conventional hypoxia markers. High-risk tumors showed distinct immunosuppressive features including reduced CD8 + T cells and elevated Th2 cells, along with significantly increased expression of immune checkpoints CD274 (PD-1, p < 0.05) and CD276 (B7-H3, r = 0.62, p < 0.001). Notably, we uncovered an unexpected inverse relationship between hypoxia-induced genomic instability and PARP inhibitor sensitivity, challenging current therapeutic paradigms. Conclusion Our methodology establishes a more precise hypoxia signature specific to HCC, advancing beyond traditional approaches. The paradoxical finding of reduced PARP inhibitor sensitivity in genomically unstable tumors reveals new complexities in hypoxia-driven treatment resistance, suggesting the need for alternative therapeutic strategies in hypoxic HCC.